Big Data and Consumer Behavior: The Power and Pitfalls of Analytics in the Digital Age - Vasilopoulou, Christina; Theodorakopoulos, Leonidas; Giannoukou, Ioanna (Technium Social Sciences Journal, 2023)
The advent of digital technology has transformed the way businesses interact with consumers, providing an abundance of data that can be harnessed to improve the customer experience. Big data analysis offers businesses the tools to gain insight into consumer behavior and preferences, optimize the customer journey, and create personalized experiences. This paper explores the impact of big data analysis on digital consumer behavior, delving into the opportunities, challenges, and ethical considerations that arise in this context.